(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This article indicates the importance of the prior choice of objects and resources for the puppet theater, since they carry meanings that constitute the dramaturgy of the show. To this end, we recount work processes that over the years allowed to deepen and radicalize this perspective, from which the matter and history of the objects come to compose the dramaturgy. All of which will be presented as a theater of exhibition, a theater where showing is an essential action.